MAGNETIC RESONANCE CHOLANGIO-PANCREATOGRAPHY EXAMINATION PROCEDURE USING BITTER TEA AND GADOLINIUM CONTRAST MEDIA IN COLELITIASIS CASES AT THE RADIOLOGY INSTALLATION OF HUSADA HOSPITAL JAKARTA - Aminadi, Zein Rizka; Susanto, Fani; Utami, Hernastiti Sedya; Saputri, Lutfiana Desy (LPPM Universitas Awal Bros, 2023)
This study aims to describe the procedures for managing MRCP examinations in cases of cholelithiasis at Husada Hospital, Jakarta. This type of research is descriptive qualitative using questionnaire sheets which are used for direct observation, documentation, interviews and literature studies, then data reduction is carried out, categorized and interpreted. Observations were carried out in May- July 2023 with the subjects of this study using 2 patients. From the results of the study it can be described that the MRCP examination technique with cholelithiasis cases at Husada Hospital Jakarta has a special preparation procedure, namely fasting for 5-6 hours and 30 minutes before the examination the patient drinks bittertea (2 sachets of tea bags/4.6 g mixed with mineral water 100 ml) added with 2 mlgadolinium contrast. Patients must first screen to ensure that there are no ferromagnetic materials, this examination uses a sequence that includes a 3-plane localizer, axial dual echo, axial T2, coronal T2, thick slab, 3D MRCP Respiratory Trigger or 3D MRCP Breath hold with time 40 minute check. MRCP examination produces Axial, Coronal and 3D sections in preparation for the patient drinking bitter tea and gadolinium with the addition of 3D MRCP RTR or 3D MRCP BH sequences which can optimally show the anatomy, physiology and abnormalities ofthe gallbladder and biliary system.